Analisis Efektifitas Sistem Informasi Perpustakaan UIN Sulthan Thaha Saifuddin Menggunakan Metode TAM - Murjoko, Murjoko; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2023)
The Implementation of the Library Information System has been carried since 2014 at UIN Sulthan Thaha Saifuddin Jambi. In its practice, not all users use the system to search online catalogs any library collection. This can be seen of visitor to the system which is small. This study aims at evaluating the effectiveness of the implementation of Library Information System. This research uses the TAM theory by using individual factors in external variables. The sample was obtained as many as 184 respondents who were declared valid. The data analysis is PLS-SEM with SmartPLS. The results of the study shows that those two variables in the TAM is perceived ease of use has a significant effect on its perceived usefulness, but the perception of its ease of use does not have a significant effect on the perceived usefulness of the system. So concluded that the easiness and its usefulness of the system have a real influence on the effectiveness of using the Library Information System. Furthermore, the external variable of acceptance consist of individual factors that have a significant effect on perceptions of usefulness and perceptions of ease of use therefore, those factors must be considered by the leader so that the Library Information System can be used effectively by users.